Information System Development of Muhammadiyah’s School in Sukoharjo Regency - Choirul Amin; Kuswadji Dwi Priyono; Danang Maulana Arif Saputra; Eko Budi Khoirul Umam (Universitas Muhammadiyah Surakarta, 2022)
Majlis Pendidikan Dasar dan Menengah (Dikdasmen) Pimpinan Daerah Muhammadiyah (PDM) Sukoharjo has hundreds of Muhammadiyah schools ranging from kindergarten, elementary, junior high school, vocational school to islamic boarding schools but does not have a database and the distribution of their locations. The purpose of this activity is to compile a database and develop a web-based Muhammadiyah school information system as a medium of information both from and to Majlis Dikdasmen PDM Sukoharjo. The method uses is school data inventory and information system development. The initial stage of the activity was in the form of database preparation by distributing school data entry forms to school principals. Furthermore, an information system is developed which includes data classification, data generalization and symbolization, making map services, and web interface design. The final result of the activity is the Muhammadiyah Sukoharjo School Information System which is on line and can be accessed at http://www.sekolahmuskh.com/. The information system make easier to access, edit, add, delete and store data, so as it easier to manage the charities owned by Majlis Dikdasmen PDM SUkoharjo. In the future, this information system still needs to be developed with a more complete and up-to-date database with current conditions in schools.